2012
DOI: 10.1128/cvi.00423-12
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Downregulates the Systemic Cytokine Response in Patients with Community-Acquired Pneumonia

Abstract: hThe influence of adjunctive corticosteroids on the cytokine response in community-acquired pneumonia (CAP) is largely unknown. In this study, we analyzed the effect of dexamethasone on the cytokine response in patients with CAP and evaluated whether this effect is dependent on the causative microorganism. We hypothesized that dexamethasone has a larger effect on the cytokine response in patients with pneumococcal pneumonia than in patients with pneumonia caused by an atypical bacterium. A total of 304 hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 17 publications
2
36
1
2
Order By: Relevance
“…In addition, IL-17A was detected in BAL fluids from Legionella pneumonia patients. The present findings suggest a clinical role for IL-17A in Legionella pneumonia, similar to the role reported in CAP associated with other bacterial pathogens (7)(8)(9). In addition, we demonstrated that the serum IL-17A levels did not correlate with the serum IFN-g or BAL fluid IL-17 levels in patients with Legionella pneumonia.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…In addition, IL-17A was detected in BAL fluids from Legionella pneumonia patients. The present findings suggest a clinical role for IL-17A in Legionella pneumonia, similar to the role reported in CAP associated with other bacterial pathogens (7)(8)(9). In addition, we demonstrated that the serum IL-17A levels did not correlate with the serum IFN-g or BAL fluid IL-17 levels in patients with Legionella pneumonia.…”
supporting
confidence: 67%
“…Recently, several groups examined the clinical roles of IL-17 in patients with community-acquired pneumonia (CAP) (7-9). Remmelts et al reported low systemic concentrations of IL-17 in CAP cases (7). Paats et al demonstrated that IL-17A was not detectable in the bronchoalveolar lavage (BAL) fluid and sera from patients with CAP (8), whereas such patients exhibited increased numbers of Th17 cells in the peripheral blood and bronchoalveolar (BA) space of patients with CAP (9).…”
mentioning
confidence: 99%
“…In our study, IL-10 levels increased significantly from 6 to 48 h in the DS group in comparison to the controls. In adults with pneumococcal pneumonia, high levels of IL-10 were present in serum at admission and declined within 48 h while treated with antibiotics (34). In another study in humans with pneumococcal pneumoniae, high levels of IL-10 increased the in-hospital mortality rate (35).…”
Section: Discussionmentioning
confidence: 97%
“…Alguns órgãos, como o pâncreas, o fígado e os rins, podem apresentar alterações morfofuncionais atribuídas à corticoterapia (Bruder et al, 2006). A dexametasona ainda exerce influência sobre a distribuição de células sanguíneas através da inibição da expressão de citocinas (Remmelts et al, 2012), redução drástica do número de linfócitos T, elevação acentuada de neutrófilos, além de uma redução acentuada dos linfócitos B, células NK (natural killer) e monócitos (Dhabhar et al, 1996).…”
Section: Introductionunclassified